Timber Portal Frames vs Timber Truss-Based Systems for Residential Buildings - Harry Far; Claire Far (Advances in Civil Engineering)
A large number of structures have been built during or after the construction of a house or residential-zoned building, which are not built at the same time and/or integrally with the structural integrity of the residential dwelling. These include carports, pergolas, sheds, and barns. The typical method of constructing these structures is a general timber truss and column system. The aim of this study is to look at the feasibility and economic incentive that may be gained from using a timber portal frame system, similar to the steel or timber portal frames used for larger industrial constructions, over the traditional timber truss and column arrangement. In this study, designs for three cases of timber truss and timber portals were carried out using industry appropriate methods and standards. Using the design information and data gathered through talks with industry professionals, both methods of construction were compared on cost and overall time duration. From the comparison of the truss and portal designs, the use of timber portal frames over timber truss systems proved to have advantage in relation to overall cost and man power involved. This could certainly affect the current attitude towards the construction of small residential buildings in the future.